Readiness of companies to implement effective tax management practices: A case study in Indonesia - Maulana, Nandi; Kurnia, Budi; Silalahi, Heriantonius (WIM Solusi Prima, 2024)
This study aims to evaluate and comprehend the gap between the tax management quality of companies in Indonesia and the effective practices of tax management. A systematic literature review was initially conducted to identify the relevant Critical Success Factors (CSFs) essential for measuring tax management quality. A comprehensive survey involving numerous businesses highlights the variability in commitment to tax strategies and the challenges companies face in integrating effective tax management principles. Key findings emphasize the importance of leadership commitment, employee training, and proactive risk management in enhancing tax practices. Despite some alignment with best practices, many companies struggle with critical areas such as employee development and the implementation of a robust tax culture. The study advocates for a holistic approach, urging companies to embed tax strategies into their overall business operations and to foster a culture of continuous improvement. Additionally, it calls on policymakers to provide regulatory support and incentives that encourage compliance and the adoption of innovative technologies. Overall, this research underscores the urgent need for Indonesian companies to elevate their tax management practices to improve compliance and enhance overall business performance.